Aging and mental health - Segal, Daniel L.; Qualls, Sarah Honn; Smyer, Michael A. (Hoboken, New Jersey Wiley Blackwell, 2018)
"The third edition of Aging and Mental Health is filled with new updates and features, including the impact of the DSM-5 on diagnosis and treatment of older adults. Like its predecessors, it uses case examples to introduce readers to the field of aging and mental health. It also provides both a synopsis of basic gerontology needed for clinical work with older adults and an analysis of several facets of aging well. Aging and Mental Health, Third Edition is an ideal text for advanced undergraduate and graduate students in psychology, for service providers in psychology, psychiatry, social work, and counseling, and for clinicians who are experienced mental health service providers but who have not had much experience working specifically with older adults and their families".--Provided by Amazon.
Part 1. Introduction. Mental health and aging: an introduction ; Basic Gerontology for working with older adults ; Psychological bases of positive mental health -- Part 2. Models of Mental Health in Later Life. Psychodynamic model with co-author Lacey Edwards ; Cognitive-behavioral model ; Stress and coping model ; Family systems model -- Part 3. Introduction to Mental Disorders. Cognitive impairment and neurocognitive disorders ; Major depression and bipolar disorder ; Serious mental disorders in older adults: Schizophrenia and other late-life psychoses / Stephen J. Bartels, Karen L. Fortuna, and John A. Naslund ; Anxiety disorders, hoarding disorder, and post-traumatic stress disorder ; Sexual disorders, sleep disorders, and chronic pain ; Substance-related disorders and personality disorders -- Part 4. Settings and Contexts of Mental Health. Health services delivery systems ; Housing, social services, and mental health ; Family and friends relationships, and caregiving ; Ethical issues in work with older adults: advanced care, financial decision-making, and the impacts of climate change.
Includes bibliographical references and index.
Keywords: Older people -- Mental health; Geriatric psychiatry